Empire of cotton: a new history of global capitalism - Beckert, Sven. (Knopf, 2014)
The epic story of the rise and fall of the empire of cotton, its centrality in the world economy, and its making and remaking of global capitalism. Sven Beckert's rich, fascinating book tells the story of how, in a remarkably brief period, European entrepreneurs and powerful statesmen recast the world's most significant manufacturing industry, combining imperial expansion and slave labor with new machines and wage workers to change the world. Here is the story of how, beginning well before the advent of machine production in the 1780s, these men captured ancient trades and skills in Asia, combined them with the expropriation of lands in the Americas and the enslavement of African workers to crucially recast the disparate realms of cotton that had existed for millennia. We see how industrial capitalism then reshaped these worlds of cotton into an empire, and how this empire transformed the world. The empire of cotton was, from the beginning, a fulcrum of constant global struggle between slaves and planters, merchants and statesmen, farmers and merchants, workers and factory owners. In this as in so many other ways, Beckert makes clear how these forces ushered in the world of modern capitalism, including the vast wealth and disturbing inequalities that are with us today. The result is a book as unsettling as it is enlightening: a book that brilliantly weaves together the story of cotton with how the present global world came to exist. From the Hardcover edition.